2018
DOI: 10.1002/hbm.24212
|View full text |Cite
|
Sign up to set email alerts
|

Animacy and real‐world size shape object representations in the human medial temporal lobes

Abstract: Identifying what an object is, and whether an object has been encountered before, is a crucial aspect of human behavior. Despite this importance, we do not yet have a complete understanding of the neural basis of these abilities. Investigations into the neural organization of human object representations have revealed category specific organization in the ventral visual stream in perceptual tasks. Interestingly, these categories fall within broader domains of organization, with reported distinctions between an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…Animate-looking (e.g., cow mug) and animate objects (e.g., cow) are dissociated in behaviour but not in the ventral visual stream measured by fMRI (Bracci et al, 2019). Chosen animacy dimensions explain variance in the ventral visual stream fMRI measurements: agency (Thorat et al, 2019), animacy (Blumenthal et al, 2018), humanlikeness (Rosenthal-von der Pütten et al, 2019), and capacity for self-movement and thought rather than face presence (Proklova & Goodale, 2020). The time course with which animacy representations emerge has been investigated with magnetoencephalography (MEG), revealing the time course of agency (Contini et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animate-looking (e.g., cow mug) and animate objects (e.g., cow) are dissociated in behaviour but not in the ventral visual stream measured by fMRI (Bracci et al, 2019). Chosen animacy dimensions explain variance in the ventral visual stream fMRI measurements: agency (Thorat et al, 2019), animacy (Blumenthal et al, 2018), humanlikeness (Rosenthal-von der Pütten et al, 2019), and capacity for self-movement and thought rather than face presence (Proklova & Goodale, 2020). The time course with which animacy representations emerge has been investigated with magnetoencephalography (MEG), revealing the time course of agency (Contini et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing animate things is essential for choosing appropriate actions as we engage the physical and social world, and can be a matter of life and death (e.g., quick recognition of a tiger in the wild). Animacy is an important representational division in nonhuman and human higher ventral visual cortical areas in the inferior temporal cortex (Kriegeskorte et al, 2008) and the medial temporal lobe (Blumenthal et al, 2018) as measured by functional magnetic resonance imaging (fMRI). Consistent with the importance of animacy perception in the classical neuropsychological literature, lesion studies established that living things are represented in dedicated regions of the cortex (Funnell & Sheridan, 1992; Ralph et al, 1998; Silveri et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…𝐿𝑜𝑔𝑎𝑟𝑖𝑡ℎ𝑚𝑖𝑐: 𝑦 = ln 𝑥 (11) where x is the value of the real-world size PC, and y is the measured real-world size of objects. The scale with the best fit was taken as the relationship that best describes the data.…”
Section: Evaluate the Role Of Real-world Size In Object Spacementioning
confidence: 99%
“…Third, fMRI studies on humans have revealed that the real-world size of objects is encoded in human's ventral temporal cortex, where the medial part of the occipitotemporal cortex is preferable to object with a larger size and the lateral to a smaller size (9). Finally, size information is apparently encoded independently from animacy, and they together form a tripartite organizational schema (i.e., big objects, all animals and small objects) in the ventral occipitotemporal cortex (10) and medial temporal lobe (11).…”
Section: Introductionmentioning
confidence: 99%
“…Third, fMRI studies on humans have revealed that the real-world size of objects is encoded in human's ventral temporal cortex, where the medial part of the occipitotemporal cortex is preferable to object with a larger size and the lateral to a smaller size 6 . Finally, size information is apparently encoded independently from animacy, and they together form a tripartite organizational schema (i.e., big objects, all animals and small objects) in the ventral occipitotemporal cortex 7 and medial temporal lobe 8 . However, the neuronal sensitivity (sensitivity criterion) to a feature is requisite, but not sufficient, for examining whether the feature serves as an axis of object space.…”
Section: Introductionmentioning
confidence: 99%